Exploring urban residents' understanding, attitudes and behaviors towards disaster waste management: A survey- based study - Syed Ismail, Sharifah Norkhadijah; Mohd Nasir, Nurul’izzah; Zainal Abidin, Emilia; Rangga, Josfirin (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2023)
Introduction: Flood waste management is a global concern as significant number of wastes are frequently shifted and mud-washed makes waste recovery extremely a daunting task. Objectives: To assess the urban residents understanding, attitudes, and behaviors towards disaster waste management. Methods: A cross-sectional study was conducted among 250 flood victims in Shah Alam, Selangor. The respondents were given a self-administered questionnaire to obtain sociodemographic characteristics, the post-flood waste management practice in the flood area, the victims knowledge and attitude in managing flood waste. Results: The major flood debris was steel, wood, clay, household furnishings, tree, and branches. The flood waste were disposed at the side of the road (n = 103, 41.2), by the disposal bins (n = 92, 36.8) and at the empty space near their house (n = 51, 20.4). The time taken to clean up the flood waste by most respondents was more than 5 days while the waste contractor took 4 to 5 days. Respondents in this study have good knowledge (n = 217, 86.8), good attitude (n=202, 80.8) and good practice (n = 222, 88.8) regarding post-flood waste management. The knowledge were associated with gender, education level, and types of media. The attitude were associated with age, education level and attitude. Education level and residential location were significantly associated with practice. The relationship between knowledge, attitude and practice can be reaffirmed. Conclusion: This study emphasizes the importance of knowledge, attitude and practice to establish systematic post-flood waste management in the urbanized setting.